The Influence of Safety Culture and Safety Behavior on Occupational Safety and Health (OHS) Performance at PT. Samudra Oceaneering - Christianus Kakambong; Chinta Yolanda Sari; Jamal Jamal; Deddy Juniawan; Aldila Syabir Raswan; Ardila Sufany (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Occupational Health and Safety (OHS) is a critical priority in high-risk industries such as oil and gas, where accidents cause serious injury and financial loss. At PT. Samudra Oceaneering, Batam, Indonesia, recurring 2024 medical cases forced employees into administrative reassignment, underscoring the operational stakes of workplace safety management. Objective: This study aimed to empirically examine the influence of safety culture and employee safety behavior on OHS performance. Method: A quantitative, cross-sectional design surveyed 101 employees using a Likert-scale questionnaire, analyzed through PLS-SEM. Result and Discussion: Results showed safety culture had a positive but non-significant effect on OHS performance (β=0.148, p=0.145), while safety behavior significantly predicted it (β=0.419, p=0.001), together explaining 25.5% of its variance. These findings indicate that safety behavior, more than cultural perception, directly drives safety outcomes in high-risk offshore settings. Conclusion: The study concludes that safety culture must be actively reinforced through leadership visibility and accountability systems to translate values into measurable safety performance